Agressividade em pacientes psiquiátricos internados - Calegaro, Vitor Crestani (2013)
The aggressiveness during the psychiatric hospitalization produces physical and psychological damage for the patients as well as for the health staff. Many researches were accomplished around the world, however the existing differences in cultural, methodological and execution places don´t allow generalization to the local reality. The aims of this research are: (1) to identify the profile of psychiatric inpatients, (2) to determine the prevalence of the aggressiveness, (3) to relate risk factors with aggressive behavior, and (4) to compare psychopathological differences among groups. It is a cross-sectional study conducted in the Hospital Universitário de Santa Maria´s Psychiatric Service, with patients admitted between August, 2012 and January, 2013, who met the inclusion criteria: (1) psychiatric hospitalization, and (2) age between 18 and 65 years-old. Patients with delirium diagnosis were excluded. A research form, the Brief Psychiatric Ratting Scale (BPRS) and the Overt Aggression Scale (OAS) were used. The study obtained Research Ethic Committee approval, and the patients signed the informed consent term. The sample was composed by 137 admissions. The prevalence of aggression in the first 24 hours was of 41.6%, for the verbal aggression, 37.2%, for physical and against objects aggression, 8.8% and for the self-aggression, 5.5%. The major risk factors were the involuntary status of hospitalization, history of any type of aggression in the week preceding admission, history of compulsive use of cannabis and cocaine, diagnostic hypothesis of multiple substance use and smoking. The aggressive patients in general exhibited higher scores on BPRS, with more activation, thought disturbances and withdrawalretardation, with less anxiety-depression. The physically aggressive presented more severe agitation and psychotic behavior (hallucinatory and delusive). The selfaggressive ones, besides this, presented more disorientation and disorganized thought, being considered the most severe patients in this study. We concluded that the aggressiveness is related to the history of aggressive behavior, history of use of substances and, mainly, to the severity of the psychopathology, being the aggression more severe as more severe are the patient´s psychosis and agitation. Too agitated patients and with severe psychotic symptoms must be observed with special caution due to the imminent risk of physical aggression against others and self-aggression.